Paleoecology of Permo-Triassic Boundary According to Palynoflora in Shourjestan, Iran - Rad, B Mostafa Yousefi; Noroozpour, Hamideh (International Journal of Geography and Geology, 2016)
Using palynoflora findings, the present study was conducted to determine paleoecology of Permo-Triassic boundary in Shourjestan Region in north of Fars Province. Permo-Triassic boundary in this region is gradational (transitional) and continuous. Four stratigraphic sections were selected and 7 spore and pollen instances were identified after sampling and performing needed experiments for separation of palynomorph samples. Based on the achieved palynomorphs on pyroclastic deposits in the studied sections, it can be concluded that Coniferophyta, Equisetopsids, Filicopsids, Progymnosperms and Cordaitales had probably higher relative frequency in plant tissue around the basin environment. According to relatively high frequency of land palynomorphs in the studied deposits and on the basis of association of land and marine palynomorphs in the studied palynoflora, it can be concluded that pyroclastic deposits of upper Permian are formed in shallow marine setting. Regarding studies on the identified palynomorphs of Elika Formation equivalent deposits, one might infer that probably in plant tissue around these deposits, Triassic seed ferns and Coniferophyta had higher frequency and distribution and also the aforementioned deposits are settled in shallow marine settings.